Pengaruh User-Generated Content dan Estetika Visual terhadap Brand Awareness Fashion Lokal - Ana Ramadhayanti (LPPM Universitas Bina Sarana Informatika, 2026)
This research seeks to examine the impact of User-Generated Content (UGC) and Visual Aesthetics on the Brand Awareness of local fashion products in online marketplaces, concentrating on the inhabitants of Koja, North Jakarta. The swift expansion of e-commerce has rendered digital aspects, like user-generated content and visual appeal, vital components in influencing consumer brand perceptions. It is thought that strong brand recognition assists local brands in competing against global products that lead the online market. This research utilized a quantitative survey method. A survey was given to 100 participants chosen through purposive sampling. The questionnaires were utilized to choose participants based on these criteria: living in Koja, aged 18 to 40, and having bought local fashion items via online marketplaces in the last six months. The data analysis utilized multiple linear regression via SPSS version 25, starting with tests for validity, reliability, and classical assumptions. The findings show that both UGC and Visual Aesthetics positively and significantly influence Brand Awareness. UGC enhances consumer trust in the brand by providing genuine, relevant, and engaging content. In the meantime, visual aesthetics significantly contribute to improving visual attractiveness, design uniformity, and consumer awareness and memory of a brand. At the same time, these two independent variables accounted for 61.2% of the increase in brand awareness for local fashion products. These results validate that combining UGC with visual appeal is a successful approach to enhancing brand recognition. Consequently, regional fashion companies are encouraged to enhance user-generated content while preserving the visual appeal of their products in the market.